Tributyrin and anise mixture supplementation improves growth performance, nutrient digestibility, jejunal villus height, and fecal microbiota in weaned pigs - Dang, De Xin; Lee, Haeun; Lee, Seung Jae; Song, Jun Ho; Mun, Seyoung; Lee, Kang Yeon; Han, Kyudong; Kim, In Ho (Frontiers in Veterinary Science, 2023)
The objective of this study was to investigate the effects of dietary supplementation of tributyrin and anise mixture (TA) on growth performance, apparent nutrient digestibility, fecal noxious gas emission, fecal score, jejunal villus height, hematology parameters, and fecal microbiota of weaned pigs. A total of 150 21-day-old crossbred weaned pigs [(Landrace × Yorkshire) × Duroc] were used in a randomized complete block design experiment. All pigs were randomly assigned to 3 groups based on the initial body weight (6.19 ± 0.29 kg). Each group had 10 replicate pens with 5 pigs (three barrows and two gilts) per pen. The experimental period was 42 days and consisted of 3 phases (phase 1, days 1-7; phase 2, days 8-21; phase 3, days 22-42). Dietary treatments were based on a corn-soybean meal-basal diet and supplemented with 0.000, 0.075, or 0.150% TA. We found that dietary supplementation of graded levels of TA linearly improved body weight, body weight gain, average daily feed intake, and feed efficiency (P < 0.05). TA supplementation also had positive effects on apparent dry matter, crude protein, and energy digestibility (P < 0.05) and jejunal villus height (P < 0.05). The emission of ammonia from feces decreased linearly with the dose of TA increased (P < 0.05). Moreover, TA supplementation was capable to regulate the fecal microbiota diversity, manifesting in a linearly increased Chao1 index and observed species and a linearly decreased Pielou's index (P < 0.05). The abundance of Lactobacillus reuteri, Lactobacillus amylovorus, Clostridium butyricum were increased, while the abundance of Prevotella copri was decreased, by treatment (P < 0.05). Therefore, we speculated that TA supplementation would improve growth performance and reduce fecal ammonia emission through improving nutrient digestibility, which was attributed to the increase of jejunal villus height and the regulation of fecal microbiota.